Normal Anatomy of the Extrinsic Capsular Wrist Ligaments by 3-T MRI and High-Resolution Ultrasonography - Taljanovic, Mihra S.; Malan, Jedidiah J.; Sheppard, Joseph E. (Seminars in Musculoskeletal Radiology, 2012)
The anatomy of the extrinsic capsular wrist ligaments is complex. These ligaments are probably as important as the intrinsic interosseous ligaments for the maintenance of carpal stability. The extrinsic capsular wrist ligaments are frequently divided into dorsal, palmar, and collateral depending on their anatomical location. They have known origin and attachment sites with recognized anatomical variants. However, there is controversy in the literature related to their anatomy and nomenclature. In the past two decades, imaging has gained an important role in the evaluation of the extrinsic capsular wrist ligaments. Both 1.5-T magnetic resonance imaging (MRI) and magnetic resonance arthrography can provide good evaluation of the extrinsic capsular wrist ligaments; 3-T MRI with improved resolution provides better visualization of the same anatomical structures. Ultrasonography using high-resolution linear transducers allows good visualization of the extrinsic capsular wrist ligaments with results that are comparable with MRI. This article describes the normal anatomy of the dorsal, palmar, and collateral extrinsic capsular wrist ligaments on 3-T MRI and high-resolution ultrasonography.
Keywords: extrinsic; capsular; ligament; MRI; ultrasonography